Annual competition for essay writing in danish language (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2021)
The annual competition for essay writing in Danish language has been organized since 2015 by the “Hans Christian Andersen Centre for Research and Information” at Sofia University “St. Kliment Ohridski”, the Embassy of Denmark in Sofia and the Danish Agency for Culture and Palaces (Slots- og Kulturstyrelsen).Every year the students from the Department of German and Scandinavian Studies who study Danish language and culture participate in the competition. The aim is to encourage students to apply their Danish language skills in a different context, broaden their perspectives and motivate them to learn even more about Denmark’s language, culture and history.This year’s essay competition was entitled “Hvordan skabes tillidsbroer?” – “How do we create bridges of trust”, commemorating the 90th anniversary of the initiation of the diplomatic relations between Bulgaria and Denmark.The first prize was awarded to Magdalena Petkova, who is a 3rd year student (Scandinavian Studies programme) and the Special prize of the Danish ambassador was awarded to Daniel Theoharov, 4th year student (Scandinavian Studies programme).